Teaching Assistants – a hit or a miss: The development of a teaching assistant programme to support academic staff at a university - Xena Michelle Cupido; Najwa Norodien-Fataar (Perspectives in Education, 2018)
Access and equity have long been fundamental concepts underpinning transformation in higher education. Increased student enrolments necessitated the implementation of support structures to bolster student success. However, support provision for academic staff is often overlooked when prioritising student success. In this article, we examine the need for academic support structures in relation to student success from the perspective of Bronfenbrenner’s ecological theory. We argue the merits of a Teaching Assistant (TA) programme to address issues related to equity of access and success by highlighting the experiences of TAs and academic staff in what can be considered constraining university structures. Based on qualitative participatory principles we collected data by means of a World Café. The paper concludes with the significant contribution made by TAs to academic staff support in addressing the challenge of equity of access and success when working collaboratively. Universities are encouraged to strengthen academic staff development through initiatives that support lecturers in creating spaces for closer student staff engagement, enhancing teaching and learning in the process.